2021
DOI: 10.1177/07334648211025116
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Lower Depression Levels in Older Adults During COVID-19 Lockdown

Abstract: Background Social distancing during the COVID-19 pandemic may lead to adverse mental health consequences, such as depression, among older adults. This study aimed to investigate the predictors of lower depression scores in older adults living under lockdown. Methods 1,123 older Brazilian adults were cross-sectionally assessed for depression, physical activity (PA), pet ownership (dogs, cats, and birds), ability to make video calls, leaving home during lockdown, and not living alone. The statistical procedures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 37 publications
4
25
0
Order By: Relevance
“…Studies have shown that older adults who were physically active did not experience an increase in depression and anxiety, or were less depressed. 13,54 Similar findings were observed for the use of social media in older adults. 12,55 Also, therapist-guided digital interventions and cognitive behavioural therapy have improved mental quality of life, reduced loneliness, and provided protection against the life stressors experienced (e.g., lockdown, pandemic).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Studies have shown that older adults who were physically active did not experience an increase in depression and anxiety, or were less depressed. 13,54 Similar findings were observed for the use of social media in older adults. 12,55 Also, therapist-guided digital interventions and cognitive behavioural therapy have improved mental quality of life, reduced loneliness, and provided protection against the life stressors experienced (e.g., lockdown, pandemic).…”
Section: Discussionsupporting
confidence: 75%
“…During the COVID‐19 pandemic, a significant amount of research was carried out about protection of mental health. Studies have shown that older adults who were physically active did not experience an increase in depression and anxiety, or were less depressed 13,54 . Similar findings were observed for the use of social media in older adults 12,55 .…”
Section: Discussionsupporting
confidence: 57%
“…Although it is highly plausible that living arrangement is related to experiencing abuse or depression, multiple studies on the COVID-19 pandemic did not detect any significant associations (Bohn et al, 2021; Chang & Levy, 2021). In our study, living arrangement (i.e., living with at least one cohabitant) was associated with higher odds of experiencing +VPC (OR = 2.70, 0.95 CI = 1.83–3.98).…”
Section: Discussionmentioning
confidence: 98%
“…To date, many studies from different countries and with different sampling strategies, sample sizes, and research designs have investigated the well-being and mental health of older populations during the pandemic. Some studies have found that older adults have a lower prevalence of depression symptoms, psychological distress, and anxiety compared to younger adults (e.g., Arpino et al, 2021 ; Bohn et al, 2021 ; Kobayashi et al, 2021 ; Taylor et al, 2021 ). However, variations in mental health and well-being in the older adult population has been understudied.…”
Section: Discussionmentioning
confidence: 99%